Adaptive FOV Control of Laparoscopes With Programmable Composed Constraints - Yang, Bohan; Chen, Wei; Wang, Zerui; Lu, Yiang; Mao, Jiayue; Wang, Hesheng; Liu, Yun-Hui (IEEE transactions on medical robotics and bionics, 2019)
Field of view (FOV) is important for minimally invasive surgeries. However, manual laparoscope manipulation is laborious and requires a lot of training. Assistants' fatigue and misunderstanding during collaboration will also compromise the quality of FOV. To improve these drawbacks, we developed a new algorithm to automatically manipulate 2-D laparoscopes. The innovative aspect lies in the following ways: the algorithm designs adaptive laws for on-line estimation of depth information, which is difficult to calibrate accurately in advance; to follow moving tools and stabilize FOV around local operations at the same time, a region-based visual servoing method is proposed. We design a novel region factor to deal with regions of different shapes; Aside from the remote center of motion (RCM), the eye-hand coordination problems, especially misorientation, are also key issues for MIS. However, how to reduce the misorientation effects is still an open problem in the literature. We propose a new constraint called the intuitive virtual plane (IVP) constraint to minimize the misorientation; in contrast with the most related works assuming the optical axis and physical axis of a laparoscope are perfectly coincident to each other, our method can be extended to different kinds of laparoscopes without any assumptions on its optical and physical axis with null-space method to decouple image-based visual servoing (IBVS) and RCM-IVP constraints. Experiments are presented to validate the method. Moreover, user studies and interviews are conducted with medical professionals and inexperienced subjects, and the results show that our system is able to improve efficiency, eye-hand coordination, and safety for FOV control of laparoscopes.